2015
DOI: 10.1167/iovs.14-15876
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin 1 (Grx1) Protects Human Retinal Pigment Epithelial Cells From Oxidative Damage by Preventing AKT Glutathionylation

Abstract: Glutaredoxin 1 can protect RPE cells against oxidative stress-induced apoptosis. The mechanism of this protection is associated with its ability to stimulate the phosphorylation of AKT by preventing AKT glutathionylation. Considering Grx1's protective abilities in RPE cells, Grx1 could be a potential pharmacological target for retinal degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…Treatment of lung fibroblasts with Fas-ligand resulted in cell death when WT-Fas, but not C294A-Fas was expressed [ 17], suggesting that glutathionylation of Fas is a pre-requisite for cell death signal transduction. In addition, glutathionylation of the cell survival kinase Akt has been associated with decreased Akt activation and reduced cell viability in the human fetal retinal pigment epithelial cells when challenged with H 2 O 2 [ 40]. Conversely, overexpression of Grx1 resulted in decreased levels of Akt glutathionylation in response to H 2 O 2 and increased activation of Akt signaling [ 40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of lung fibroblasts with Fas-ligand resulted in cell death when WT-Fas, but not C294A-Fas was expressed [ 17], suggesting that glutathionylation of Fas is a pre-requisite for cell death signal transduction. In addition, glutathionylation of the cell survival kinase Akt has been associated with decreased Akt activation and reduced cell viability in the human fetal retinal pigment epithelial cells when challenged with H 2 O 2 [ 40]. Conversely, overexpression of Grx1 resulted in decreased levels of Akt glutathionylation in response to H 2 O 2 and increased activation of Akt signaling [ 40].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the context of Grx1 deficiency, it is important to note that Akt1 has been reported in other contexts to be regulated both directly [40] and likely indirectly [46] through reversible protein glutathionylation. Thus, treatment of human retinal pigment epithelial cells with H 2 O 2 resulted in Akt1 glutathionylation, impaired phosphorylation of Akt1, and cell death [40]. Over-expression of Grx1 resulted in decreased levels of glutathionylated Akt1, normalized phosphorylation/activation of Akt1, and increased cell viability when challenged with H 2 O 2 [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group also found that Grx1 protected lens epithelial cells from oxidative stress by reactivating the oxidatively-inactivated glyceraldehyde 3-phosphate dehydrogenase (G3PD) through dethiolation [15]. Grx1 is also critical for protecting human RPE cells against oxidative stress, and our previous study has shown that Grx1 overexpression protected RPE cells from H 2 O 2 -induced apoptosis by stimulating AKT phosphorylation through prevention of AKT glutathionylation [16]. Considering Grx1’s protective abilities in RPE cells, Grx1 could be a potential pharmacological target for retinal degenerative diseases, like AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GRX-1 was reported to be able to control the glutathionylation of molecules implicated in LPS-or IL-1β-stimulated signaling pathways in a variety of cell types. GRX-1 suppresses oxidative stress-induced AKT glutathionylation and apoptosis in human retinal pigment epithelial cells [38]. It also regulates IL-1-mediated glutathionylation of TNF receptor-associated factor 6, an intermediate molecule involved in the IL-1R and TLR4 signaling pathways [39].…”
Section: Discussionmentioning
confidence: 99%